2018
DOI: 10.1111/jcmm.13846
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of apoptosis‐related microRNAs following myocardial infarction in fat‐1 transgenic mice vs wild‐type mice

Abstract: BackgroundmicroRNAs (miRNAs) post‐transcriptionally regulate cardiac repair following myocardial infarction (MI). Omega‐3 polyunsaturated fatty acid (ω‐3 PUFAs) may support cardiac healing after MI, but the mechanism is unclear.MethodsThe fat‐1 transgenic mouse expresses a ω‐3 fatty acid desaturase which converts ω‐6 PUFAs to ω‐3 PUFAs in vivo. MI was induced in fat‐1 transgenic (n = 30) and wild‐type (WT) mice (n = 30) using permanent ligation. Other transgenic and WT mice underwent sham procedure (n = 30 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Downregulation of miRNA-21 after consumption of PUFAs was also observed in other studies of animal models and cell cultures [100,101]. Ma et al [102] concluded that omega-3 PUFAs may have a protective effect on cardiomyocytes following myocardial infarction through their upregulation of anti-apoptotic miRNAs (miRNA-133a-5p, miRNA-149-5p, miRNA-208a-3p) and downregulation of pro-apoptotic miRNAs (miRNA-210-3p). Zheng et al [94] reported that omega-3 PUFAs regulate miRNA-19b, -146b and -183 in Wistar rats.…”
Section: The Modulation Of Mirnas By Dietary Components In Cardiovsupporting
confidence: 59%
“…Downregulation of miRNA-21 after consumption of PUFAs was also observed in other studies of animal models and cell cultures [100,101]. Ma et al [102] concluded that omega-3 PUFAs may have a protective effect on cardiomyocytes following myocardial infarction through their upregulation of anti-apoptotic miRNAs (miRNA-133a-5p, miRNA-149-5p, miRNA-208a-3p) and downregulation of pro-apoptotic miRNAs (miRNA-210-3p). Zheng et al [94] reported that omega-3 PUFAs regulate miRNA-19b, -146b and -183 in Wistar rats.…”
Section: The Modulation Of Mirnas By Dietary Components In Cardiovsupporting
confidence: 59%
“…Various nutritional components can modulate the expression of diverse miRNAs [ 3 ]. Omega-3 PUFAs, for example, protect cardiomyocytes after an MI by upregulating the anti-apoptotic miRNAs and downregulating the pro-apoptotic miRNAs [ 28 , 29 ]. Flaxseed is the richest source of the plant-based omega-3 PUFA, ALA. Dietary supplementation with flaxseed has demonstrated anti-arrhythmic, antiatherogenic, antihypertensive, and cholesterol-lowering effects in animal and human studies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that miRNAs played important roles in physiological and pathological processes, including cell cycle regulation [1], cell differentiation [1] in ammatory responses [2], apoptosis [3] and extracellular matrix (ECM) degradation [4]. Upgraded serum miRNA-204 (miR-204) levels have been regarded as associated with insulinoma [5], acute lymphocytic leukemia [6], human breast cancer [7] and other tumors [8].…”
Section: Introductionmentioning
confidence: 99%